The tribology handbook - Neale, M. J. (Michael John). (Oxford ; Boston : Butterworth-Heinemann, 1995)
The renowned reference work is a practical guide to the selection and design of the components of machines and to their lubrication. It has been completely revised for this second edition by leading experts in the area.
Contents include: Bearings; Drives and seals; Lubricants; Lubrication and working conditions; Component failures, maintenance and repair; Basic tribology and design reference.
Includes index.
Keywords: Tribology -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc